Nate Smith [compact disc] - Smith, Nate (Musician) (Arista Nashville, 2023)
The first thing Nate Smith said when asked about his debut, self-titled album was, "It's not about me. It's about being able to reach other people with music that means something." Nate's mission with his music is to be a "conduit of hope"; a selfless and passionate driving force that's thematic in his songs. "I'm not trying to be cool, or reinvent the wheel, or chase musical trends... I'm going after the heart of the matter." The result is a refreshing and timeless body of work. His journey to Nashville and the challenges he endured along the way are traceable in his gravelly tone: heartbreak, losing his hometown of Paradise, CA to the deadliest and most destructive fire in the state's history, and a determined crosscountry road trip to Music City that often involved sleeping in his car. Nevertheless, he found purpose and hope through it all. Like Nate, the 20-song collection is honest, raw, real, and threaded together with optimism. He fearlessly takes on vulnerability, a characteristic evident not only in his lyrics, but also in his fragile yet robust delivery. While each song tells its own story, Nate unveils two sides of his artistry through the project: deep, heartfelt ballads and fun-loving, drink in the air, country jams. The two are intertwined with undeniable hooks and his signature velvet thunder vocals.